Uji Laboratorium : Pengaruh Konsentrasi Pour Point Depressant (PPD) terhadap Pour Point Crude Oil pada Sumur ST-X - Khaerul Rohman; Baiq Maulinda Ulfah (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
ST-X crude oil exhibits waxy characteristics with an initial pour point of 22°C, which is very close to the field fluid temperature of 21.1°C, potentially causing flow disturbances and paraffin crystal formation. This study aims to evaluate the effect of varying concentrations of Pour Point Depressant (PPD) on pour point reduction through laboratory testing. A 1-Liter crude oil sample was divided into five portions (0.2 L each) and injected with PPD at concentrations of 5, 10, 15, 20, and 25 ppm, followed by cooling bath testing to determine the pour point values. The results indicate that increasing PPD concentration progressively reduced the pour point, reaching 13°C at 25 ppm. From technical and economic perspectives, 10 ppm is recommended as the optimum dosage, as it effectively maintains oil flowability under field operating conditions.